Trauma and envenoming caused by stingrays and other fish in a fishing community in Pontal do Paranapanema, state of São Paulo, Brazil: epidemiology, clinical aspects, and therapeutic and preventive measures - Vidal Haddad Junior; Edson Luiz Fávero Junior; Felipe Augusto Horácio Ribeiro; Bruno da Costa Ancheschi; Gabriel Isaac Pereira de Castro; Rafael Costa Martins; Guilherme Borghini Pazuelo; Jun Ricardo Fujii; Rodolfo Brum Vieira; Domingos Garrone Neto (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: Accidents caused by fish are common in inland fishing communities in Brazil, being work-related injuries in the majority of cases. These populations have no information on the mechanisms of trauma or envenoming. METHODS: Through a questionnaire administered to fishermen, we obtained clinical and epidemiological data on accidents in Rosana, Pontal do Paranapanema, State of São Paulo, Brazil. These data were analyzed and converted into an easily understood prevention and treatment program for the colony. RESULTS: Thirty-nine fishermen replied to the survey. All of the patients had been hurt by fish. Of those mentioned, the yellow catfish (Pimelodus maculatus) was the main fish species associated with injuries, but others also caused trauma to the fishermen. Six fishermen had been envenomed by stingrays. Pain and ulcers were the main symptoms and were described as intolerable. Approximately half of those injured were treated using traditional folk remedies. CONCLUSIONS: The fishermen suffered multiple accidents with catfish, which are venomous and cause intense pain, as well as trauma due to other fish, such as surubins, traíras, freshwater croakers, and piranhas. Approximately 16% of those interviewed presented with envenomation from stingrays. Our data and previous experience in the area led to the creation of a pamphlet with clear language that can effectively help fishermen in the region, an area in need of health services and disease prevention. This initiative also applies to the whole La Plata River basin, which has similar fauna.